2015
DOI: 10.1007/s11845-015-1270-0
|View full text |Cite
|
Sign up to set email alerts
|

Effective communication enhances the patients’ endoscopy experience

Abstract: Structured information leaflets and improved staff communication skills reduce anxiety and enhance patients' experiences. They are now standard operating procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Previous research has shown that patients with experience of several colonoscopies particularly value the interaction, continuity, and the technical skill of the physician more than for example, patients admitted for a screening colonoscopy [8,[13][14][15][16]. Clear and concise information before and during the colonoscopy have important and positive effects on worries and pain before and during the procedure [15][16][17]. Waiting time and the surrounding environment during the visit are also factors of importance for satisfaction with the colonoscopy [14,18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that patients with experience of several colonoscopies particularly value the interaction, continuity, and the technical skill of the physician more than for example, patients admitted for a screening colonoscopy [8,[13][14][15][16]. Clear and concise information before and during the colonoscopy have important and positive effects on worries and pain before and during the procedure [15][16][17]. Waiting time and the surrounding environment during the visit are also factors of importance for satisfaction with the colonoscopy [14,18].…”
Section: Introductionmentioning
confidence: 99%
“…Even though efforts have been made to reduce the invasiveness of this technique, colonoscopy still presents a risk of severe complications (especially during IBD exacerbations), 5 and a general physical and psychological discomfort is common in patients who have to undergo this examination. [6][7][8] In addition, this invasive methodology is restricted to the diagnostics of superficial changes on the Supplemental digital content is available for this article. Direct URL citations appear in the printed text and are provided in the HTML and PDF versions of this article on the journal's Web site (www.ibdjournal.org).…”
mentioning
confidence: 99%
“…17 An interesting observation reported in a similar study is that longer waiting times before receiving procedural information are correlated with higher anxiety. 21 In our research, self-assessed levels of knowledge were not associated with discomfort. This result may be due to the fact that the patients described their level of knowledge about gastroscopy as moderate, and the knowledge that they have more often comes from friends and family than from the physician.…”
Section: Resultsmentioning
confidence: 39%
“…Some studies suggest that reliable information before a gastroscopy has a positive influence on the patient's distressing feelings. 19,20 Although informational leaflets are successful at reducing anxiety, 21 oral information seems to be more effective. 17 An interesting observation reported in a similar study is that longer waiting times before receiving procedural information are correlated with higher anxiety.…”
Section: Resultsmentioning
confidence: 99%